Hydrogen spillover in the Fischer-Tropsch synthesis: the role of platinum and gold as promoters in cobalt-based catalysts - Nabaho, Doreen (Centre for Catalysis Research, 2015)
The Low Temperature Fischer-Tropsch (LTFT) synthesis involves the catalytic hydrogenation of carbon monoxide with the aim to produce long-chained hydrocarbons. Commercial cobalt-based catalysts incorporate oxidic supports that are known to negatively affect the reducibility and hinder formation of the active phase. Consequently, reduction promoters such as Pt are introduced to facilitate the reduction of cobalt during catalyst pretreatment. However, synergistic and adverse effects of the promoter have been reported under reaction conditions including a higher site-time yield and higher selectivity towards hydrogenated products. The perspective on the operation of the Pt promoter is polarised between 'Hydrogen spillover', which is a so-called remote-control effect that could otherwise occur in the absence of Pt-Co contact, and 'ligand/electronic effects' that require direct Pt-Co coordination. The objective of this study was to explicate the operation of Pt and Au as promoters of the Co/Al2O3 catalyst by decoupling hydrogen spillover from effects that require direct promotercobalt coordination. The analysis was subdivided into the reduction process and the Fischer- Tropsch reaction, which are the two arenas in which the actions of these promoters have been claimed. The employment of model 'hybrid' catalysts, which are mechanical mixtures of the monometallic constituents of the promoted catalyst, presents a novel way to investigate the role of spillover hydrogen in the Pt-Co and Au-Co catalyst systems. Thus far, no systematic investigation of the hydrogen spillover phenomenon using these catalyst systems during both reduction and under commercially relevant LTFT conditions has been encountered in the published literature. Furthermore, this study serves to contribute to the limited body of literature on the role of Au as a potential promoter for the commercial cobalt-based catalyst.